Answer:
2x+59.
Step-by-step explanation:
Let J represent Jessica's weight and R represent Ronda's weight.
Jessica weighs x+34 pounds. Thus:
[tex]J=x+34[/tex]
Ronda weighs 12 pounds less than Jessica. In other words:
[tex]R=J-12=(x+34)-12\\R=x+22[/tex]
The sum of their weights, therefore, is:
[tex]J+R\\=(x+34)+(x+22)=2x+56[/tex]
Now, if Jessica gains 5 pounds and Ronda loses 2 pounds, the net gain of the total weight would be 3 pounds. Thus, we only need to add 3 to the original total to find the sum of their new weights:
[tex]2x+56+3=2x+59[/tex]
The sum of the new [weights] is represented by 2x+59.